ESSENTIAL OIL OF THYMUS PECTINATUS FISCH&MEY.VAR.PECTINATUS: CHEMICAL FORMATION, ANTIMICROBIAL, ANTIOXIDANT, ANTISPASMODIC AND ANGIOGENIC ACTIVITIES - Saygın, Ayşegül Göze; Göze, İsmihan; Alim, Ahmet; Ercan, Nazlı; Durmuş, Nedim; Vural, Nilufer; Alim, Betül Aycan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Thymus species are well-known as medicinal plants. It was aimed to investigate the chemical composition of Thymus pectinatus (TP) and its antioxidant, antimicrobial, antispasmodic, and angiogenic activities. Materials and Methods: After essential oil of TP (EO-TP) was obtained with clevenger distillation system, it was analyzed for chemical composition with GC-MS. To study antispasmodic activity, eight male Wistar albino rats each weighing approximately 250-300 g were used. Results: The results of the analysis revealed 19 components, which equals to 92.93 of the essential oil. The following are the main components; thymol (48.77%), m-cymene (9.15%), isoborneol (5.19%), trans-caryophyllene (4.43%), carvacrol (3.91%) and -terpinene (3.54%). It has been found that microorganisms subjected to whole all of microbiological tests are highly resistant to EO-TP. 2,2- diphenyl-l-picrylhydrazyl, hydroxyl radical, along with superoxide radical scavenging, and lipid peroxidation says were utilized to show the antioxidant activities of the EO-TP. In measuring its effect, 0.1 mg/mL and 0.5 mg/mL dosage of the EO-TP was applied to the rat ileum as a result of which the magnitude and the frequency of the contractions were observed to be significantly. Conclusion: It was also understood that EO-TP had angiogenic effect upon the vein system of the embryos of chicks. There is a need for further studies to clarify the mechanisms of antimicrobial, antioxidant and angiogenic effects and to determine the constituents of EO-TP responsible from these effects, especially the angiogenic.